Canon and canonization in García Márquez’s work - González-Ortega, Nelson (Tropelías: Review of Literary Theory and Comparative Literature, 1999)
An analysis of the literary work as well as the journalism and the cinematography of Gabriel García Márquez reveals the presence of two main autorial concerns: 1) the literary strategy adopted by the autor and his narrators for textualizing the hagiographical and secular practices of "canonization", and 2) the use of parody, as a literary device, to question the (de)formalion of Colombia’s literary and historical canon. Due to the fact that these literary aspects of García Marquez’s work have not been investigated in a systematic way, I propose in this essay to identify the thematic and technical strategies used by the Colombian author and his narrators to transpose fïccionally in his texts the cultural practices of both "sacred (religious) canonization" and "secular (historical and literary) canonization" as a means to "deconstruct" Colombia’s offïcial concept of national history and literature. This study is based on the theoretical concepts of E. Sullà ("canon formation"), A. Gramsci y M. Foucault ("official discourse"), and B. Anderson ("nation and nationalism").